Sérový amyloid A jako efektivní marker stupne operacní záteze a rizika komplikací - Jabor, A; Holub, Z; Franeková, J; Pavlisová, M; Boril, P; Fenclová, E; Kliment, L (Ceska gynekologie, 2006)
OBJECTIVE: To analyze relations among acute phase reactants in a group of 40 women operated for uterine myom by laparoscopy and open surgery. DESIGN: Prospective study. METHODS: Plasma concentrations of C-reactive protein (CRP), serum amyloid A (SAA) and interleukin 6 (IL-6) were measured together with leukocytes in blood before operation, 24 and 72 hours post operation, respectively. RESULTS: Leukocytes and IL-6 displayed minimal response and decreased quickly after operation to preoperative levels. Concentrations of CRP and SAA remained increased after operation. There were no relationships between leukocytes and acute phase reactants. Normal leukocytes 72 hours post operation were found in 1/3 of women with increased at least one acute phase reactants and in 1/4 of women with increased at least two markers. Typ of surgery, surgical stress and length of surgery were related to the concentration of CRP, IL-6 and SAA. CONCLUSION: Changes in SAA 24 hours after operation are similar to CRP and IL-6. Surgical stress, length of operation and possible risk 72 hours after operation are best predicted by CRP and SAA (at that time IL-6 and leukocytes are practically normal). Maximal increase was found for SAA concentrations. Thus SAA seems to be suitable marker of early postoperative complications.
Keywords: fyziologický stres; nádory dělohy; Humans; lidé středního věku; počet leukocytů; C-reaktivní protein; reakce akutní fáze; Gynecologic Surgical Procedures; gynekologické chirurgické výkony; Postoperative Period; Acute-Phase Reaction; Female; Interleukin-6; dospělí; Leiomyoma; leiomyom; lidé; Biomarkers; Leukocyte Count; Stress, Physiological; Uterine Neoplasms; Adult; Postoperative Complications; pooperační komplikace; biologické markery; ženské pohlaví; Middle Aged; interleukin-6; sérový amyloid A; Serum Amyloid A Protein; pooperační období; C-Reactive Protein